Case report: Novel NIPBL-BEND2 fusion gene identified in osteoblastoma-like phosphaturic mesenchymal tumor of the fibula - Sakai, Tomohisa; Okuno, Yusuke; Murakami, Norihiro; Shimoyama, Yoshie; Imagama, Shiro; Nishida, Yoshihiro (Frontiers in Oncology, 2023)
Phosphaturic mesenchymal tumor (PMT) is a rare tumor that secretes fibroblast growth factor 23 (FGF23) and causes hypophosphatemia and tumor-induced osteomalacia (TIO). Fusion genes FN1-FGFR1 and FN1-FGF1 have been detected in some PMTs, but the pathogenesis of PMTs without these fusion genes remains unclear. Here, we report a 12-year-old boy with persistent muscle weakness and gait disturbance. Roentgenographic examination revealed a radiolucent lesion with endosteal scalloping in the left fibula, while his serum level of FGF23 was markedly increased. Combined with simple X-ray findings of other body parts, we suspected that TIO was caused by PMT, and resected the tumor. After resection, the serum level of FGF23 started to decrease immediately and normalized within 3 hours after resection, with this being earlier than normalization of the serum phosphorus level. In RNA sequencing, FN1-FGFR1 and FN1-FGF1 were not detected, but a novel NIPBL-BEND2 fusion gene was identified. When we forcedly expressed this fusion gene in HEK293T cells and MG63 cells, cell proliferation was enhanced in both cell lines. Furthermore, Gene set enrichment analysis of HEK293T cells showed significant upregulation of MYC-target genes. Our results suggest that this novel NIPBL-BEND2 fusion gene promotes cell proliferation possibly via the MYC pathway and might be one of the etiologies of PMTs other than FN1-FGFR1 or FN1-FGF1.